Folic Acid–Conjugated PLGA Nanoparticles of Eugenol: Development, Characterization, and In Vitro Cytotoxicity Studies on Breast Cancer Cell Line. - Kashyap, Bhawna; Khan, Azhar; Malik, Tabarak; Kapoor, Deepak N.; Banerjee, Baisakhi (BioMed Research International, 2026)
Background: The primary goal of the study was to develop folic acid–conjugated eugenol‐loaded PLGA nanoparticles for the treatment of breast cancer. Eugenol is reported to have potent anticancer activity. Entrapment of eugenol in folic acid–conjugated polymeric nanoparticles is expected to enhance its availability at the cancer site and improve overall efficacy in breast cancer treatment. Method: Eugenol was isolated by the column chromatography technique. The isolated bioactive fraction was characterized by IR and NMR analyses. Polymeric NPs were prepared by the solvent emulsification–diffusion method and conjugated with FA by the EDC coupling method. The in vitro release profile for FA‐conjugated eugenol‐loaded PLGA NPs was evaluated by the dialysis membrane technique. Further in vitro anti‐inflammatory activity, in vitro antioxidant assays, and cytotoxicity studies were carried out. Results: NPs exhibiting particle size ranging from 444.2 to 928.3 nm, zeta potential ranging from −32.0 to −37.7 mV, entrapment efficiency ranging from 76.97% to 87.51%, and percent conjugation were found to be 72.59%–79.68%. The in vitro drug release profiles of the formulations were most effectively described by the Higuchi kinetic model, indicating that the mechanism governing drug release is primarily attributed to diffusion. The FTIR study indicated that there is no chemical modification of the drug, confirming its compatibility with other excipients. The morphology of the NPs was analyzed by FESEM analysis. The particulate nature of NPs showed homogenous, spherical shapes of NPs. The cell cytotoxicity studies on MDA‐MB‐231 cell lines exhibited enhanced cytotoxicity of the NPs. Conclusion: In conclusion, it was found that FA‐conjugated PLGA NPs can be a suitable platform for the targeted administration of eugenol for BC treatment.